Consumer Green Products through the Lens of Bibliometrics: Trends analysis - Shafie, Nani Ilyana; Abd Rahman, Nurul Hayani; Harun, Rabitah; Ismail, Shaira; Shafie, Nur Aliaa (Information Management and Business Review, 2024)
The growth of articles is reflected in the increasing interdisciplinary research and publications on consumer green products. Scholars from fields as diverse as business, management and accounting, environmental science, social science, and engineering have contributed to more than 400 publications. This article aims to understand the growth of green consumer products by using bibliometric analysis. With the limitation set only for the final stage and English used, a total of 1961 articles were published in the Scopus database from 1990 to 2024. The analysis of document and source types, top keywords, and other bibliometric indicators was explained. In addition, Publish or Perish software was used to analyze citation metrics and highly cited articles. As the global focus on sustainability intensifies, research in this field will likely continue to grow. Future studies should lengthen this work to other article databases such as WOS and Google Scholar to understand how consumer green products can contribute to a more sustainable business future. Besides that, the researcher also can explore how the green marketing mix influences consumer intention to purchase green products available in the market.